It’s Not Just About Age Anymore:: The Unpardonable Sin of Forgetfulness Within and Beyond the 2024 U.S. Elections - de Medeiros, Kate (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
The U.S. presidential elections have been the site of racism, sexism, classism, ableism, and ageism among other problematic issues. While the 2024 U.S. presidential election continues to be fraught with numerous “isms” and accusations, the focus in this essay is on a new and powerful discrediting tactic: the whisper of cognitive decline. Accusations of cognitive decline not only cast doubt on a politician’s ability to think and act clearly—an unpardonable sin in leadership—but also builds on ageist stereotypes that make such accusations seem credible despite evidence. Ultimately, I argue that because Donald Trump and Joe Biden are wealthy, white, educated men of roughly similar ages, seventy-seven and eighty-one respectively, targeting their cognitive status feeds into social stigmas and fears that are difficult to counter and that, unfortunately, the harm caused by this new level of attack negatively affects older people and people living with neurocognitive disorders.